It looks like you're new here. If you want to get involved, click one of these buttons!

- All Categories 2.3K
- Chat 499
- Study Groups 19
- Petri Nets 9
- Epidemiology 4
- Leaf Modeling 1
- Review Sections 9
- MIT 2020: Programming with Categories 51
- MIT 2020: Lectures 20
- MIT 2020: Exercises 25
- MIT 2019: Applied Category Theory 339
- MIT 2019: Lectures 79
- MIT 2019: Exercises 149
- MIT 2019: Chat 50
- UCR ACT Seminar 4
- General 69
- Azimuth Code Project 110
- Statistical methods 4
- Drafts 2
- Math Syntax Demos 15
- Wiki - Latest Changes 3
- Strategy 113
- Azimuth Project 1.1K
- - Spam 1
- News and Information 148
- Azimuth Blog 149
- - Conventions and Policies 21
- - Questions 43
- Azimuth Wiki 713

Options

The string of inequalities in Eq. (2.15) is not quite a proof, because technically there is no such thing as \( v + w + u \), for example. Instead, there is \( (v+w)+u \) and \( v+(w+u) \), and so on.

- Formally prove, using only the rules of symmetric monoidal preorders ( Definition 2.2 ), that given the assertions in Eq. (2.13), the conclusion in Eq. (2.14) follows.
- Reflexivity and transitivity should show up in your proof. Make sure you are explicit about where they do.
- How can you look at the wiring diagram Eq. (2.6) and know that the commutative axiom (Definition 2.1 d.) does not need to be invoked?

**Eq 2.15** \( t + u \le v + w + u \le v + x + z \le y + z \)

**Eq 2.14** \( t + u \le y + z \)

**Eq 2.13** \(t \le v + w \) and \( w + u \le x + z \) and \( v + x \le y \)

## Comments

I tried to sketch a proof, but I don't know if it is correct. Let us start from the first assertion of (2.7), that is, \(t \le (v+w)\). We can write \((v+w) \le (v+w)+u\), that is `more rich.' By part (c) of Definition 2.1, we can write \((v+w)+u = v + (w+u)\). Using the second assertion in (2.7), we have: \(v + (w+u) \le v + (x+z)\). By (c), we get \(v + (x+z)=(v+x)+z\). Considering the third assertion, we can write \((v+x)+z\le y +z\). Let us go back to the first assertion: \(t \le (v+w)\); this implies \((t + u)\le (v+w)+u\). But \((v+w)+u\le y +z\), and thus, by transitivity, \((t + u)\le (y+z)\).

I have been thinking of other solutions. Wire \(t\) in diagram 2.4 branches into \(v+w\). I'm wondering if we might re-write \(t \le v + w\) as \(t+0 \le v+w\). I'm also wondering if we can consider this as the combination of \(t \le v\) and \(0 \le w\), `reversing' point (a) of Definition 2.1. In the same way, we can find \(w \le x\), \(u \le z\), as well as \(v \le y\) and \(x \le 0\). We have \(t \le v \le y\) and, by transitivity, \(t \le y\). Let us now just consider \(t \le y\) and \( u \le z\). By point (a), we get \(t+u \le y+z\), that is Eq. 2.8.

If we look at the wiring diagram, I guess that we do not need part (d) of Def. 2.1 because the wires do not twist.

`I tried to sketch a proof, but I don't know if it is correct. Let us start from the first assertion of (2.7), that is, \\(t \le (v+w)\\). We can write \\((v+w) \le (v+w)+u\\), that is `more rich.' By part (c) of Definition 2.1, we can write \\((v+w)+u = v + (w+u)\\). Using the second assertion in (2.7), we have: \\(v + (w+u) \le v + (x+z)\\). By (c), we get \\(v + (x+z)=(v+x)+z\\). Considering the third assertion, we can write \\((v+x)+z\le y +z\\). Let us go back to the first assertion: \\(t \le (v+w)\\); this implies \\((t + u)\le (v+w)+u\\). But \\((v+w)+u\le y +z\\), and thus, by transitivity, \\((t + u)\le (y+z)\\). I have been thinking of other solutions. Wire \\(t\\) in diagram 2.4 branches into \\(v+w\\). I'm wondering if we might re-write \\(t \le v + w\\) as \\(t+0 \le v+w\\). I'm also wondering if we can consider this as the combination of \\(t \le v\\) and \\(0 \le w\\), `reversing' point (a) of Definition 2.1. In the same way, we can find \\(w \le x\\), \\(u \le z\\), as well as \\(v \le y\\) and \\(x \le 0\\). We have \\(t \le v \le y\\) and, by transitivity, \\(t \le y\\). Let us now just consider \\(t \le y\\) and \\( u \le z\\). By point (a), we get \\(t+u \le y+z\\), that is Eq. 2.8. If we look at the wiring diagram, I guess that we do not need part (d) of Def. 2.1 because the wires do not twist.`

The approach suggested by Eq. 2.9 is that as a "cut line" moves from left to right as each inequality is "cut" a inequality is expressed. Put another way, the application of 2.1.a produces an implication. Throughout the proof \( + = \otimes \).

Given \( t + u \)

By 2.1.a \( x_1 = t , x_2 = u, y_1 = v + w , y_2 = u \) and 2.7.a \( t \le v + w \) giving \( t + u \le (v + w) + u \).

Applying 2.1.c we get \((v + w) + u = v + (w + u) \).

By 2.1.a \( x_1 = v, x_2 = w + u , y_1 = v, y_2 = x + z \) and 2.7.b \( w + u \le x + z \) giving \( v + (w + u) \le v + (x + z) \).

Applying 2.1.c we get \( v + (x + z) = (v + x) + z \).

By 2.1.a \( x_1 = v + x, x_2 = z, y_1 = y, y_2 = z \) and 2.7.c \( v + x \le y \) giving \( (v + x) + z \le y + z \).

`The approach suggested by Eq. 2.9 is that as a "cut line" moves from left to right as each inequality is "cut" a inequality is expressed. Put another way, the application of 2.1.a produces an implication. Throughout the proof \\( + = \otimes \\). Given \\( t + u \\) By 2.1.a \\( x_1 = t , x_2 = u, y_1 = v + w , y_2 = u \\) and 2.7.a \\( t \le v + w \\) giving \\( t + u \le (v + w) + u \\). Applying 2.1.c we get \\((v + w) + u = v + (w + u) \\). By 2.1.a \\( x_1 = v, x_2 = w + u , y_1 = v, y_2 = x + z \\) and 2.7.b \\( w + u \le x + z \\) giving \\( v + (w + u) \le v + (x + z) \\). Applying 2.1.c we get \\( v + (x + z) = (v + x) + z \\). By 2.1.a \\( x_1 = v + x, x_2 = z, y_1 = y, y_2 = z \\) and 2.7.c \\( v + x \le y \\) giving \\( (v + x) + z \le y + z \\).`

Thanks! This is very clear. I'm wondering if the first part of my sketch was correct, even if much longer.

`Thanks! This is very clear. I'm wondering if the first part of my sketch was correct, even if much longer.`

WIP

$$(v + w) + u \le (x + v) + z$$ $$(v + w) + u \le y + z$$ $$t + u \le y + z$$

`WIP $$(v + w) + u \le (x + v) + z$$ $$(v + w) + u \le y + z$$ $$t + u \le y + z$$`